2018
DOI: 10.1002/ldr.2849
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing our options: Managing water‐limited soils for conservation and restoration

Abstract: The Food and Agriculture Organization considers around a quarter of global land to be degraded. Of particular concern are threats to soils in water‐limited regions, which are critical to food and economic security in countries across the globe but are under increasing pressure due to human use and climatic forcing. These soils have been used to feed and provide resources and services to human societies for millennia, with earliest land‐uses dating back to prehistoric times. With the adoption of modern, frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 139 publications
(200 reference statements)
0
10
0
2
Order By: Relevance
“…Whereas some researchers argued that rotational grazing had a positive (e.g., Conant et al, 2003; Sanderman et al, 2015) or insignificant influence (e.g., Briske et al, 2008; Chan et al, 2010) on SOC, others showed that rotational grazing increased livestock production (Badgery, Millar, Michalk, Cranney, & Broadfoot, 2017) and reduced bare ground and the impact of grazing on grassland (Teague et al, 2011). The greater economic benefits (compared to exclusion) and better vegetation conditions (compared to continuous grazing) make rotational grazing a viable alternative short‐term management method (Hobley, Garcia‐Franco, Hübner, & Wiesmeier, 2018). This is supported by Xiong, Shi, Zhang, and Zou (2016), who suggested that grazing exclusion should be integrated with sustainable management (e.g., rotational grazing or periodic grazing).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some researchers argued that rotational grazing had a positive (e.g., Conant et al, 2003; Sanderman et al, 2015) or insignificant influence (e.g., Briske et al, 2008; Chan et al, 2010) on SOC, others showed that rotational grazing increased livestock production (Badgery, Millar, Michalk, Cranney, & Broadfoot, 2017) and reduced bare ground and the impact of grazing on grassland (Teague et al, 2011). The greater economic benefits (compared to exclusion) and better vegetation conditions (compared to continuous grazing) make rotational grazing a viable alternative short‐term management method (Hobley, Garcia‐Franco, Hübner, & Wiesmeier, 2018). This is supported by Xiong, Shi, Zhang, and Zou (2016), who suggested that grazing exclusion should be integrated with sustainable management (e.g., rotational grazing or periodic grazing).…”
Section: Discussionmentioning
confidence: 99%
“…Os atributos químicos do solo são influenciados diretamente pelas práticas agrícolas, de forma a ser é imprescindível a observação e avaliação dos impactos pela sua utilização (Hobley et al, 2018). Haja visto que, as características do solo apresentarão explicações relevantes sobre a qualidade do solo, onde o acompanhamento é de fundamental importância para determinar o manejo e uso adequado para cada tipo de solo, especialmente em regiões mais suscetíveis à degradação, como os solos do semiárido brasileiro (Ayangbenro & Babalola, 2020).…”
Section: Indicadores De Impactos Em áReas De Sequeirounclassified
“…Além disso, essas alterações são capazes de promover variações nas emissões de gases para a atmosfera. O tipo de manejo pode conservar ou aumentar as quantidades de carbono orgânico no solo, favorecendo a eficiência produtiva e a mitigação das emissões de CO2 para a atmosfera (Hobley et al, 2018).…”
Section: Indicadores De Impactos Em áReas De Sequeirounclassified
“…Revegetation has been for many years a conventional strategy for rehabilitation of degrading landscapes (Hobley et al, 2018) and using native plants adapted to drought can facilitate plant establishment in degraded soils under moisture stress conditions (Bateman et al, 2018).…”
mentioning
confidence: 99%
“…A group of articles in this issue, is focused on revegation techniques. Revegetation has been for many years a conventional strategy for rehabilitation of degrading landscapes (Hobley et al, 2018) and using native plants adapted to drought can facilitate plant establishment in degraded soils under water stress conditions (Bateman et al, 2018). Revegetation efforts generally result in improvement of soil fertility and enhancement of ecosystem services and functions such as carbon sequestration (Gao et al, 2018), nutrient cycling (Barliza et al, 2018Hu et al, 2018 and soil microbial diversity and activity (García et al, 2018;Liu et al, 2019); nevertheless, it can also lead to adverse effects such as salinity which may affect the success of restoration efforts in the long term (Yu and Wang, 2018).…”
mentioning
confidence: 99%